Prevalence of Caudal Block and Duration of Analgesia of Caudal Dexmedetomidine Adjunct in Pediatric Lower Abdominal Surgery - Baral, Bidur Kumar; Poudel, Puspa Raj; Shah Malla, Sadichhya (Journal of Nepal Health Research Council, 2024)
Background: Caudal block is a commonly used method of postoperative pain management in children. However, single shot caudal block has shorter duration of analgesia that can be extended by addition of adjuncts like opioids, clonididine, and dexmedetomidine along with local anesthetics. Recently, dexmedetomidine has been used as an adjunct for prolonging the duration of analgesia. This study aimed to find out prevalence of the caudal block and the duration of analgesia with dexmedetomidine adjunct among children undergoing lower abdominal surgeries. Methods: A cross-sectional, observational study was conducted among the children admitted to the tertiary care children hospital of Nepal during the period of six months. Children of age 2 to 7 years, who had undergone lower abdominal surgeries under general anesthesia were enrolled in the study. We observed the prevalence of the caudal block and duration of analgesia of caudal dexmedetomidine with ropivacaine Results: Throughout the study period, 449 children were posted for lower abdominal surgeries. Out of which 226 children (50.03%) received caudal block. Among the caudal block, 51 children (22.56%)) were administered ropivacaine with dexmedetomidine, 45 children (19.91%) received ropivacaine alone, 43 children (19.02%) were given bupivacaine alone, 46 children (20.35%) received a combination of bupivacaine and fentanyl, and 41 children (18.14%) received bupivacaine and dexmedetomidine. Dexmedetomidine with ropivacaine provides 840.35Â±14.97 minutes of postoperative pain relief. Conclusions: The prevalence of the caudal block was 50.03%, and the combination of Dexmedetomidine with ropivacaine provides longer duration of postoperative analgesia. Keywords: Analgesia; caudal block; children; prevalence.